THE INFLUENCE OF THERMOMECHANICAL EFFECTS ON THE STRENGTH AND STABILITY OF MULTI-SPAN BEAMS - Akhmedov B.I.; Nuraliyev A.X. (Uzbekistan Open Conference, 2025)
This paper examines the influence of thermomechanical effects on the strength and stability of multi-span beams, which are widely used in construction. Temperature influences and their influence on stresses and deformations in structures are analyzed. A comprehensive numerical modeling methodology is provided, including finite element methods to account for thermal and mechanical loads.
Keywords: thermomechanical effects; strength; stability; multi-span beams; temperature effects; stress